Intelligent path selection algorithm for tactical communication networks enhanced by link state awareness - Shen, Yigang; Xie, Lei; Li, Ming (Frontiers in Communications and Networks, 2025)
In tactical communication networks, highly dynamic topologies and frequent data exchanges create complex spatiotemporal dependencies among link states. However, most existing intelligent routing algorithms rely on simplified model architectures and fail to capture these spatiotemporal correlations, resulting in limited situational awareness and poor adaptability under dynamic network conditions. To address these challenges, this study proposes an intelligent path selection method—Deep Reinforcement Learning with Spatiotemporal-aware Link State Guidance Algorithm (DRLSGA). The algorithm builds upon the Proximal Policy Optimization (PPO) framework to develop an intelligent decision-making model and integrates a link state feature extraction module that combines Gated Recurrent Units (GRU) and a Graph Attention Network (GAT). This design enables the model to learn long-term temporal dependencies and spatial structural relationships from sequential link state data, thereby enhancing perception and decision-making capability. An attention mechanism is further introduced to highlight salient features within link state sequences, while an optimal routing strategy is derived through a deep reinforcement learning-based training process. Experimental results demonstrate that, compared with the existing DRL-ST algorithm, DRLSGA reduces average end-to-end latency by at least 2.07%, lowers the packet loss rate by 1.65%, and increases average throughput by up to 2.59% under high-traffic conditions. Moreover, the proposed algorithm exhibits stronger adaptability to highly dynamic network topologies.